Comparing the Effectiveness of Study Methods and Time Management Training on Academic Self-Regulation Among Male and Female Students - Saman Azari , Jafar; Livarjani, Sholeh; Azmoodeh , Masoumeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective:  The current article aims to compare the effectiveness of study methods and time management training on the academic self-regulation of students.Methods and Materials: The research method was quasi-experimental, employing a pre-test-post-test design with a control group. The population consisted of all twelfth-grade male and female students in Tabriz schools during the academic year 2021-2022. Fifty-two students were selected as the sample through single-stage cluster sampling and were assigned into two groups: experimental (26 students, including 13 females and 13 males) and control (26 students, including 13 females and 13 males). The Savari and Arabzadeh questionnaire was used to measure academic self-regulation. Before the intervention, a pre-test of academic self-regulation was conducted for both groups. The experimental group received training on study methods and time management through an educational package in eight sessions, while the control group did not receive any educational intervention. After the intervention, in the post-test phase, both groups again answered the pre-test instrument. Data were analyzed using one-way multivariate and two-way multivariate analysis of covariance tests.Findings:  The results of the two-way multivariate analysis of covariance also indicated that the training on study methods and time management was effective on the academic self-regulation of both male and female students and its sub-scales. It showed a higher effectiveness in overall self-regulation and particularly in the help-seeking sub-scale among males (p < 0.05). For other sub-scales of academic self-regulation, the effectiveness of study methods and time management training was at the same level for both genders (p < 0.008).Conclusion:  Therefore, it can be concluded that training in study methods and time management can be used as an effective intervention for high school students.